The Obligation to Provide Iddah Maintenance in Article 152 of the Compilation of Islamic Law - Rosihin Rosihin; Syamsu Madyan; Nur Hasan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
As stipulated in Islam, marital responsibilities will remain even after the marriage ends. Therefore, the term "maintenance" is known. The provision of maintenance is divided into two types: maintenance provided within marriage and maintenance provided outside of marriage. One type of maintenance provided outside of marriage is the iddah maintenance, which is the mandatory maintenance provided to the wife during her iddah period. However, its implementation deviates from the rules. The purpose of this study is to confirm the obligation of iddah maintenance for husbands. This type of research is an empirical juridical study with a case study approach. The research technique was conducted through observation and interviews with informants in Demangan Village, Bangkalan, using descriptive qualitative analysis techniques. Analyzing the applicable regulations, it is clear that the provisions of maintenance are well-regulated. However, in reality, many residents of Demangan Village deviate and refuse to fulfill their maintenance obligations. This study contributes to strengthening the sense of responsibility of providing iddah maintenance for husbands to their ex-wives during the iddah period of divorce